The Diagnosis and Treatment of Multiple Factitious Oral Ulcers in a 6-Year-Old Boy - Priscilla Santana Pinto Gonçalves; Daniela Alejandra Cusicanqui Mendez; Paulo Sérgio da Silva Santos; José Humberto Damante; Daniela Rios; Thiago Cruvinel (Case Reports in Dentistry)
Factitious ulcers are characterized by self-inflicted lesions with multifactorial origin. These lesions are frequently found in head, neck, and hands. This report shows a 6-year-old boy diagnosed with factitious oral ulcers that occurred after the self-biting of buccal vestibule and nail-scratching of gingival tissue. Clinically, a significant swelling was observed, hard on palpation, located at the right lower third of the face, next to the posterior area of the mandible. In the intraoral examination, ulcers at different healing stages were noted on the swelling area. During the anamnesis, the father reported a change in his familial structure that triggers psychological stress, providing the clues to the presumptive diagnosis of factitious oral ulcers. We prescribed the topical use of Gingilone® three times a day to control the local pain and inflammation. At 7-day follow-up, we noticed the reduction of extraoral swelling and the initial healing of the ulcers. The presumptive diagnosis was confirmed at 30-day follow-up, with the lasting remission of oral lesions. The treatments of factitious oral ulcers should be individually tailored for each patient, focused on a multidisciplinary approach, including psychotherapy and periodic clinical control. To the best of our knowledge, gaps of evidence lead to the lack of standardized clinical protocols on this issue.